Volume 4A: Combustion, Fuels and Emissions 2017
DOI: 10.1115/gt2017-64149
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of the Internal Flow in a Pressure Swirl Atomizer

Abstract: The internal flow and discharge parameters of a pressure swirl atomizer (PSA) are numerically investigated using a coupled Level-Set (LS)/Volume-of-Fluid (VOF) solver that combines the advantages of LS and algebraic VOF methods by maintaining the mass conservation and the interface sharpness simultaneously. Internal flow velocity profile and discharge parameters including discharge coefficient, film thickness, and spray cone angle are compared between simulation results and the experimental data that are avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The inlet fuel line was also equipped with the temperature sensor (5) PR-13 with an error of 0.2°C made by OMEGA Engineering, Inc., Norwalk, Connecticut, USA. The SL contained a ball valve (11) and positive displacement flowmeter KOBOLD DOM-S05 (KOBOLD Messring GmbH, Hofheim am Taunus, Germany)] with accuracy +/-1% of the actual flowrate (12). The atomized liquid was collected in a chamber and routed back into the fuel tank.…”
Section: B Test Benchmentioning
confidence: 99%
See 1 more Smart Citation
“…The inlet fuel line was also equipped with the temperature sensor (5) PR-13 with an error of 0.2°C made by OMEGA Engineering, Inc., Norwalk, Connecticut, USA. The SL contained a ball valve (11) and positive displacement flowmeter KOBOLD DOM-S05 (KOBOLD Messring GmbH, Hofheim am Taunus, Germany)] with accuracy +/-1% of the actual flowrate (12). The atomized liquid was collected in a chamber and routed back into the fuel tank.…”
Section: B Test Benchmentioning
confidence: 99%
“…Cooper et al [10] have shown that differently shaped swirl-chamber geometries lead to different internal flow patterns. Xue et al [11] and Qian et al [12] numerically studied the effect of the convergence angle of the conical swirl chamber on both the discharge coefficient and SCA. However, they did not study the effect on the spray.…”
mentioning
confidence: 99%
“…They also noted that the flow field was consistent for LES and k-ε model, while, surprisingly, the RSM had some discrepancies. Qian [9] found RSM to be superior over the laminar model at Re = 16,000, while Nouri-Borujerdi [10] found opposite conclusions for even larger Re in range of 18,000-40,000. Baharanchi et al [11] examined several schemes to capture the liquid-air interface using a 2D simulation with RNG k-ε turbulence model.…”
Section: Introductionmentioning
confidence: 97%
“…The internal vortex behaves as a Rankine vortex since the swirl velocity has its maximum located at the air-core surface which behaves like a virtual solid cylinder [1]. Secondary flow effects, as Görtler vortices, could be also presented in a boundary layer inside the swirl chamber [2,3].…”
Section: Introductionmentioning
confidence: 99%